Constructivistic didactics in physics: implementations - Karwasz, Grzegorz; Kamińska, Anna (Acta Universitatis Nicolai Copernici. Pedagogika, 2020)
Cognitive strategies in teaching physics in Poland were first introduced in late 90’s. The first exhibition in the interactive form, was devoted to interactive physics - "Physics and Toys" in 1998 and "Contemporary Physics" in 2003 (founded at the University of Pomerania in Slupsk). Later, more comprehensive, interdisciplinary exhibitions were created at the Nicolaus Copernicus University. The success of this teaching method exceeded our expectations. We discuss the principles and practical methods of innovative didactics based on constructivist and cognitive theories. The two main paradigms of this teaching method are based on constructing the knowledge and competences of students (listeners, students) in interactive narrative and using real teaching subjects that can be pulled out of pocket. We call these concepts hyper-constructivism and neo-realism.